2021
DOI: 10.1038/s41598-021-00340-4
|View full text |Cite
|
Sign up to set email alerts
|

Marine heatwaves in the Humboldt current system: from 5-day localized warming to year-long El Niños

Abstract: During the last 4 decades punctual occurrences of extreme ocean temperatures, known as marine heatwaves (MHWs), have been regularly disrupting the coastal ecosystem of the Peru-Chile eastern boundary upwelling system. In fact, this coastal system and biodiversity hot-spot is regularly impacted by El Niño events, whose variability has been related to the longest and most intense MHWs in the world ocean. However the intensively studied El Niños tend to overshadow the MHWs of shorter duration that are significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 44 publications
0
16
0
4
Order By: Relevance
“…Extreme El Niño (Cai et al, 2018) and La Niña (Cai et al, 2015) events are also expected to increase in frequency due to climate change. Marine heatwaves (spanning 30-100 days) also show an increase in intensity and duration in the last decades in the HCS (Pietri et al, 2021). It is plausible to expect shifts in species distribution associated with these extreme events.…”
Section: Impacts Of Thermal Fluctuations Food Availability Advection ...mentioning
confidence: 99%
“…Extreme El Niño (Cai et al, 2018) and La Niña (Cai et al, 2015) events are also expected to increase in frequency due to climate change. Marine heatwaves (spanning 30-100 days) also show an increase in intensity and duration in the last decades in the HCS (Pietri et al, 2021). It is plausible to expect shifts in species distribution associated with these extreme events.…”
Section: Impacts Of Thermal Fluctuations Food Availability Advection ...mentioning
confidence: 99%
“…Work by Schlegel et al (2017a) using in situ coastal data records found that the coastal MHWs detected were typically associated with onshore or alongshore winds and anomalously high air temperature, with direct atmospheric forcing of coastal MHWs singled out as a driver that requires further investigation. Local wind relaxation events in upwelling zones have also recently been found to establish short-lived MHWs in coastal regions (Pietri et al, 2021). Further, it is apparent that the drivers of MHW occurrence can vary considerably with distance from the coastline.…”
Section: Introductionmentioning
confidence: 97%
“…For example, MHWs lasted for 251 days from 2015 to 2016 and reached a maximum intensity of 2.9°C above the climatology over the Tasman Sea (Oliver et al., 2017). A total of 426 MHWs were identified over the west coast of South America from 1982 to 2019, which lasted from 5 to 610 days and spatially covered 625–5,625,000 km 2 (Pietri et al., 2021). On a global scale, MHW duration and intensity increased by 84% and 65%, respectively, between 1982–1998 and 2000–2016 (Oliver et al., 2018).…”
Section: Introductionmentioning
confidence: 99%